Strategies to combat antimicrobial resistance in Indian scenario - RAHAL, ANU; KUMAR, AMIT (The Indian Journal of Animal Sciences, 2021)
Antimicrobial resistance (AMR) is one of the major public health crisis recognised globally. Microbial infections cause significant productivity losses in animals and humans. In livestock, these microbial infections reduce the growth rates and fertility, diminish production of meat and milk, and occasionally lead to mortality, and are therefore, a major concern for animal welfare. In the dearth of alternative prophylactic measures, antibiotics remain the principal tool for their management. Once an antibiotic is used rampantly, resistance against it is inevidently seen in the microbe population and the hunt for a new drug grows. Discovery and development of a new antimicrobial drug is a time taking and expensive procedure with limited assurance of success. As a result, the past few decades have witnessed only a very few new classes of antibiotics. If the AMR can be restricted or reverted, the success rate of antimicrobial therapy can be boosted and many public health issues be avoided. All these ask for a comprehensive plan to prevent or reduce the antimicrobial resistance and economic losses to the animal husbandry sector. The present review provides an overview of AMR in India, mechanism of its occurrence and the possible roadmap to combat the emerging threat of AMR in Indian scenario.